Preparation of Operating Manuals - C. I. Wilmot; A. Sass; J. VanDeBeuken (Society for Mining, Metallurgy & Exploration, 1986)
Introduction This chapter addresses the need for operation manuals, presents an outline as a guide for writing the manual, discusses who should write the manual, suggests how it is implemented and gives tips to potential manual writers. Theory & Purpose of Operating Manuals The primary objective of the operating manual is to provide every operator the benefit of a uniform minimum level of training. This training is not only critical to the safety and efficiency of every employee, but also provides a basis for incorporating future operational improvements into standard and emergency procedures. The manual promotes safety through- out and additionally has a special section devoted to safety. The operator should be able to find information on chemical and physical hazards as well as be exposed to safety procedures for such items as motor lockouts and tank entries. The operating manual will usually reference a separate safety manual or incorporate parts of the safety manual. Safety is also promoted through standardized procedures for operation of equipment. Standardized operation is the second most important reason for the writing of manuals. If equipment is started, operated, and shut down in a consistent manner, then operational efficiency should be maximized. If it is not, then the procedure is adjusted until it is. The experience of many can be condensed into set responses for start up, shutdown, steady state operations, and upsets. Implicit with the standardized operation objective is a minimum level of training the operator will receive by thorough familiarization with the manual. The ability to know the contents of the manual is a basic requirement for operator status. The operating manual serves as a basis for a training program both at the start of the new plant and as new operators are hired or promoted into the job. The operating manual is a collection of at least part of the knowledge that "key people" own and will cushion the loss of key personnel for whatever reason. The manual can only fulfill these lofty goals by being a dynamic document. Manuals must change as equipment is modified and superior techniques evolve. To be effective they must be periodically updated, so word processors and reproduction